The Power of Systems How Policy Sciences Opened Up the Cold War World - Rindzeviciute, Egle (Cornell University Press, 2016)
The International Institute of Applied Systems Analysis (IIASA), an international think tank established jointly by the United States and Soviet Union in Austria in 1972, was intended to advance scientific collaboration. Until the late 1980s, the IIASA was one of the very few permanent sites where policy scientists from both sides of the Iron Curtain could work together to articulate and solve world problems, most notably global climate change. One of the best-kept secrets of the Cold War, this think tank was a rare zone of freedom, communication, and negotiation, where leading Soviet scientists could try out their innovative ideas, benefit from access to Western literature, and develop social networks, thus paving the way for some of the key science and policy breakthroughs of the twentieth century.